How significant is the radiation exposure during electrophysiology study and ablation procedures for supraventricular tachycardia? - Bagchi, Avishek (Indian Heart J, 2021)
Radiation exposure during electrophysiology procedures has been a point of discussion. We measured the ionising radiation dosage during ablation procedures for supraventricular tachycardia. This was compared with coronary angiographies performed via the radial route to put it in perspective. We found that the radiation dosage during the ablation procedure was far lower, less than forty percent of that during coronary angiography (Air Kerma 249.1 mGy ± 266.95 mGy v/s 671.9 mGy ± 328.6 mGy; p < 0.001).